Geoarchaeology of Taman Peninsula (Kerch Strait, South-West Russia) – the Example of the Ancient Greek Settlement of Golubitskaya 2 - Kelterbaum, Daniel; Brückner, Helmut; Porotov, Alexey; Schlotzhauer, Udo; Zhuravlev, Denis (DIE ERDE – Journal of the Geographical Society of Berlin, 2011)
In the framework of an extensive archaeological survey and excavation programme on Taman Peninsula, geoarchaeological research was carried out in this terra incognita of the north-eastern Black Sea region. In the present study, a small area was surveyed in detail with respect to its geomorphological and archaeological situation. Geoarchaeological scenarios were generated for the last seven millennia. For the first time, the sea level rise and its effect on the landscape could be documented in time and space, showing, among others, that Taman Peninsula had evolved out of an archipelago.